The Mobilization Of Metal Elements Against The Incidence Of Dermatitis Is Seen From Community Knowledge In The Mining Circle In Amonggedo Sub-District, Konawe District : Dermatitis Is Seen From Community Knowledge - Noviati, Noviati; Ramdan, Muhammad; Sya`ban, Abdul Rahim; Juslan (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Mining activities in Amonggedo sub-district have an impact on public health and environmental conditions, including data on the 10 highest diseases in the Amonggedo Health Center work area after the presence of mining activities showing 2 types of diseases due to metal distribution that have continued to increase in the last 3 years, namely Skin Disease and Underground Tissue. Methods: The study was conducted with the Mix Method, namely descriptive analysis with water and metal quality checks carried out at the Health Laboratory of Southeast Sulawesi province and Cross Sectional research was carried out on the people of Amonggedo District, Konawe Regency. Results: The results showed that the knowledge variable obtained the value of X2 calculated > X2 table (25.235 > 3.841) which means that there is a relationship between knowledge and the incidence of dermatitis in the Working Area of the Amonggedo Health Center, Amonggedo District, Konawe Regency. Conclusions: Metal content in dominant soil elements exceeds the threshold value both at the inlet and outlet, namely Ni, Fe, Mg, Al, Si, Ca, Cr, Metal content in some elements exceeds the threshold value both at the inlet and outlet, namely TSS, Fe, Ni, Co, Pb, There is a moderate relationship between knowledge and the incidence of dermatitis in the Working Area of the Amonggedo Health Center, Amonggedo District, Konawe Regency.